Kristusovo telo in njegova golota: uveljavitev motiva - Mikuž, Jure (Monitor ISH, 2006)
Had the witness of the Passion ever seen Christ naked? Did not meditations of women (and some men as well) linger too long on Christ's loincloth (perizonium) and on what supposedly lay beneath it? These were the questions often posed in the later Middle Ages. The sleeveless tunic (colobium) attributed to Christ in the earliest depictions of the Passion came to be replaced by the loincloth, first in Byzantine art and later also in the Western art of the 11th and 12th centuries. The loincloth, either tightly woven or translucent, became a conventional sign of Christ's nakedness, serving as a censoriship covering for genitals and a fetishistic object par excellence.
Keywords: Jezus Kristus; srednjeveška umetnost; pasijon; umetnostna zgodovina; art history; likovni motivi; golota; Kristus